The performance of cross-linked acellular arterial scaffolds as vascular grafts; pre-clinical testing in direct and isolation loop circulatory models - Pennel, Timothy (Division of Cardiology, 2016)
There is a significant need for small diameter vascular grafts to be used in peripheral vascular surgery; however autologous grafts are not always available, synthetic grafts perform poorly and allografts and xenografts degenerate, dilate and calcify after implantation. We hypothesized that chemical stabilization of acellular xenogenic arteries would generate off-the-shelf grafts resistant to thrombosis, dilatation and calcification. To test this hypothesis, we decellularized porcine renal arteries, stabilized elastin with pentagalloyl glucose and collagen with carbodiimide/activated heparin and implanted them as trans- position grafts in the abdominal aorta of rats as direct implants and separately as indirect, isolation-loop implants. All implants resulted in high patency and animal survival rates, ubiquitous encapsulation within a vascularized collagenous capsule, and exhibited lack of lumen thrombogenicity and no graft wall calcification. Peri-anastomotic neo-intimal tissue overgrowth was a normal occurrence in direct implants; however this reaction was circumvented in indirect implants. Notably, implantation of non- treated control scaffolds exhibited marked graft dilatation and elastin degeneration; however PGG significantly reduced elastin degradation and prevented aneurismal dilatation of vascular grafts. Overall these results point to the outstanding potential of crosslinked arterial scaffolds as small diameter vascular grafts.